(Pro)renin receptor aggravates myocardial pyroptosis in diabetic cardiomyopathy through AMPK-NLRP3 pathway - Li, Shengnan; Zhang, Jingjing; Zhao, Yuewen; Kang, Li; Jie, Haipeng; Dong, Bo (Frontiers in Pharmacology, 2024)
Introduction As one of the most common complications of diabetes, diabetic cardiomyopathy (DCM) is the main cause of heart failure in patients with diabetes. However, the lack of effective treatments for DCM remains a clinical challenge. (Pro) renin receptor (PRR) is a member of renin angiotensin aldosterone system (RAAS). Here, we aim to determine whether PRR is involved in myocardial pyroptosis in diabetic cardiomyopathy. Methods We established diabetic rats model by intraperitoneal injection of streptozotocin (STZ). PRR overexpression adenovirus or PRR knockdown adenovirus was injected into the tail vein. Western blot, histopathology and immunohistochemistry staining, ELISA and Echocardiography were used to detect cardiac function changes and myocardial injury levels of DCM rats. Primary cardiomyocytes were stimulated with high glucose and PRR overexpression or PRR knockdown was achieved by adenovirus transfection, we also used the inhibitor of AMPK to decrease the activity of AMPK. Western blot, Real-time PCR, Immunofluorescence and ELISA were used to detect the level of PRR and pyroptosis in cardiomyocyte. Results We found that high glucose increased the expression of PRR in heart. After overexpression of PRR, the expression of the pyroptosis related proteins such as Caspase-1, IL-1β, IL-18, and NLRP3 was significantly increased, the phosphorylation level of AMPK was significantly decreased, and the fibrosis level was significantly increased, thus aggravating the cardiac function injury of DCM. On the contrary, PRR knockdown can alleviate the level of myocardial pyroptosis in DCM and improve cardiac function. The related mechanism was that PRR could inhibit AMPK phosphorylation and promote the activation of NLRP3 inflammasome. Discussion PRR aggravated pyroptosis of cardiomyocyte, increased the dysfunction of cardiomyocyte, and may be related to the decrease of AMPK phosphorylation and the overactivation of NLRP3. This may provide new ideas and targets for the treatment of DCM.